2017
DOI: 10.1088/1748-3190/aa9a0f
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the role of beamwidth in biological and engineered sonar

Abstract: Sonar is an important sensory modality for engineers as well as in nature. In engineering, sonar is the dominating modality for underwater sensing. In biology, it is likely to have been a central factor behind the unprecedented evolutionary success of bats, a highly diverse group that accounts for over 20% of all mammal species. However, it remains unclear to what extent engineered and biosonar follow similar design and operational principles. In the current work, the key sonar design characteristic of beamwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This could be due to physical constraints on changes that can be made to the shapes of a noseleaf or pinna, how much these changes can influence the beampatterns, and how different beampatterns are possible. A recent study [34] has shown that bat biosonar beampatterns are more variable than a random reference (irregular cones made from crumpled aluminum foil) in terms of beamwidth which could be seen as an indication that factors other than beamwidth have driven the evolution of these characteristics.…”
Section: IV Discussionmentioning
confidence: 99%
“…This could be due to physical constraints on changes that can be made to the shapes of a noseleaf or pinna, how much these changes can influence the beampatterns, and how different beampatterns are possible. A recent study [34] has shown that bat biosonar beampatterns are more variable than a random reference (irregular cones made from crumpled aluminum foil) in terms of beamwidth which could be seen as an indication that factors other than beamwidth have driven the evolution of these characteristics.…”
Section: IV Discussionmentioning
confidence: 99%
“…This suggests that beamwidth may not be as much of a limiting factor for bats navigating in narrow foliage as it may have appeared from the conventional approach to detecting gaps. Hence, the comparatively large beamwidths of bats that are due to the small sizes of the animals relative to the employed ultrasonic wavelengths [12], are not necessarily an obstacle to navigating through narrow gaps in vegetation. As a consequence, factors that favor narrower biosonar beams, especially larger pinnae or the use of higher frequencies, may not have offered selective advantages to these species-at least not in the context of finding passageways in vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…in Euderma, to 212 kHz, e.g. Cloeotis, [11]), bat biosonar has to make do with emission and reception half-power (−6 dB) beamwidths that are typically range from 10 • to over 100 • [12]. Even for bat species that are known to navigate in dense vegetation, beamwidths values of 12 • -18 • , e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the flying route, a total of 12 sampling points were taken. At each sampling point, the direction of the sonar beam was designed to target at the trees, and the beamwidth of the sonar was randomly sampled from the interval of PLOS ONE [30,65] degrees, a range that was found to be common for bat's biosonar [53]. Fig 7 demonstrates a bird view of the scene along with the -3 dB contours of the sonar beams (highlighted in red) and the resulting impulse responses.…”
Section: Plos Onementioning
confidence: 99%